Effect of shape on cellular uptake of visible-light- and redox-responsive biodegradable linear-dendritic block copolymer micelles - Avhad, Shankarrao V.; Ambade, Ashootosh V. (Biomacromolecules, 2026)
Linear-dendritic block copolymers comprising poly(epsilon-caprolactone) attached to hydrophilic 2,2-bis(hydroxymethyl)propionic acid (bis-MPA) ester dendron via a disulfide and containing a defined number of pendent visible-light-responsive donor-acceptor Stenhouse adduct (DASA) groups are synthesized using click chemistry and postpolymerization modification. Self-assembly in aqueous solution selectively affords rice grain-like ellipsoidal, rod-like, and spherical micelles, governed by the number of DASA groups. Progressive disassembly of the micelles is observed during photoswitching cycles. Release of camptothecin depends on the DASA content under light irradiation and is enhanced by the synergistic effect of two stimuli. Cellular uptake quantified by FACS analysis is demonstrated to be influenced by the shape of the micelles, with ellipsoidal micelles exhibiting higher efficiency than spherical micelles by following clathrin- and caveolae-mediated endocytosis as major pathways for internalization. Both types of micelles were found to maintain the particle size in Dulbecco's modified Eagle's medium containing 10% fetal bovine serum at 37 degrees C. Doxorubicin (DOX)-loaded ellipsoidal micelles under photoirradiation show significantly higher apoptosis than free DOX.